2013
DOI: 10.3109/13880209.2013.764327
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of some mushrooms in Turkey

Abstract: Context: Terfezia boudieri Chatin (Pezizaceae), Agaricus brunnescens Peck (Agaricaceae) and Lactarius vellereus (Fr.) Fr. (Russulaceae) are well-known species in Turkey, and are used both for food and traditional medicine. Objective: The powdered fruit bodies of T. boudieri, A. brunnescens and L. vellereus were used to evaluate the antimicrobial activities. Materials and methods: Chloroform, acetone and methanol extracts of T. boudieri, A. brunnescens and L. vellereus were tested for their antimicrobial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The chloroform extract of T. boudieri exhibited the strongest minimum inhibitory concentration (MIC 2.4 µg/ml) value against the test microorganism, Streptococcus pyogenes. Maximum antimicrobial effects were observed with the acetone extracts of T. boudieri and L. vellereus (MIC 4.8 µg/ml) against Bacillus subtilis (Doğan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The chloroform extract of T. boudieri exhibited the strongest minimum inhibitory concentration (MIC 2.4 µg/ml) value against the test microorganism, Streptococcus pyogenes. Maximum antimicrobial effects were observed with the acetone extracts of T. boudieri and L. vellereus (MIC 4.8 µg/ml) against Bacillus subtilis (Doğan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fr originated from Black Sea Region of Turkey possessed high antistaphylococcal activity in the chloroform and acetone extracts with a MIC value of 39 µg/mL. The author reported that a MIC value of less than 100 µg/mL was an indicator for high inhibitory activity [83].…”
Section: Antistaphylococcal Natural Products From Basidiomycetesmentioning
confidence: 99%
“…The metabolites responsible for the antistaphylococcal activities are 2,4-dihydroxybenzoic (14) and protocatechuic acid (15) [81]. Fruiting body extract of A. brunnescens prepared in chloroform and acetone solvents showed a higher antistaphylocccal activity with MIC value lower than 100 µg/mL [83].…”
Section: Antistaphylococcal Natural Products From Basidiomycetesmentioning
confidence: 99%
“…Hungary methanol extracts of A. brunnescens exhibited antifungal activity against Candida albicans at MIC 39, 19, 39 mg/mL, respectively(Doğan et al, 2013).…”
mentioning
confidence: 96%